Combination Effect of Culture Media and Silver Nanoparticle on the Effectiveness of Tobacco Anther Regeneration - Nur Khozin, Mohammad; Ahnaf, Yusuf Dary; Dewanti, Parawita; Restanto, Didik Pudji; Iryono (Bogor Agricultural University, Indonesia, 2026)
Anther culture is an effective biotechnological approach to accelerate the production of homozygous lines in tobacco breeding. This study evaluated the interaction between culture media (Murashige and Skoog/MS and Chu’s N6) and silver nanoparticle (AgNP) concentrations on in vitro anther regeneration of tobacco (Nicotiana tabacum L.). The experiment was arranged in a completely randomized design with ten treatment combinations consisting of two basal media and five AgNP concentrations (0, 2.5, 5, 7.5, and 10 ppm), each replicated three times. Quantitative parameters included callus formation, shoot regeneration, rooting response, regeneration percentage, and contamination rate. MS medium supplemented with 2.5 ppm AgNPs (K2) produced the optimal response, showing 100% callus formation and the highest shoot regeneration percentage (89%). Root formation was observed only in treatments K2 and K4. In contrast, higher AgNP concentrations (≥7.5 ppm), particularly in Chu’s N6 medium, significantly reduced regeneration percentages (ANOVA, p<0.05). The promotive effect of low AgNP concentration is associated with suppression of ethylene activity, antimicrobial action, and regulation of reactive oxygen species (ROS), which collectively enhance cell division and organogenesis. These findings indicate that MS medium supplemented with 2.5 ppm AgNPs is optimal for tobacco anther regeneration and suitable for doubled-haploid production.